Eksistensi Homo Neandertal dan Homo Sapiens Sapiens dalam Perspektif Sains dan Al-Qur’an - Tomi Apra Santosa Santosa (Universitas Nahdlatul Ulama Surabaya, 2020)
This research aims to find out the existence of Homo neandertal and Homo sapiens from the perspective of science and the Qur'an. This research is qualitative research with library study methods. Namely the presentation of data by tracing Islamic and scientific manuscripts in the form of books, journals, and so on, combining, analyzing, and drawing conclusions. The results of the study area in the science of Homo neandertal is a human species thought to be the ancestor of ancient Europe. In the Qur'an homo neandertal is Al-basyar which has been mentioned by Allah in surah Al-Baqarah verse 30. Homo Sapien sapiens were modern ancient humans who were the ancestors of the Mongols and Melanesians. In the Qur'an, Homo sapiens sapiens is thought to be the evolution of the previous man to become the caliph on earth as God said in Surah Noah 14, 17, and Surah As-Shaad verse 26.